Analisis Pengaruh Produk Domestik Regional Bruto, Upah dan Pengangguran terhadap Investasi di Wilayah Mamminasata - Wibowo, Jatayu Lingga Utari; Kafrawi Mahmud, Ahmad (ICOR: Journal of Regional Economics, 2024)
Economic development has a stage that must be carried out in every nation because it will pass through economic development in the implementation of economic activities that will run more smoothly and be able to accelerate economic growth. With anticipated investment, production capacity can increase as capital stock increases. Therefore, this study aims to analyze the effect of gross regional domestic product, wages and unemployment on investment in the Mamminasata Region. This study is quantitative. This type of data in this research uses panel data, which is a combination of time series data and cross-section data. Data were obtained from the Central Statistical Agency (BPS), Regional Basic Information and Data Management System (Simreg Bappenas), the Regional Government (PEMDA), and the Capital Investment Coordination Agency (BKPM) between 2019-2021. The analysis method used is an analysis of panel data regression using the help of Eviews 10. The estimation results show that: the gross regional domestic product variable has a positive and significant impact directly on investment in the Mamminasata region, the wage variable has a negative effect and is not directly significant in the Mamminasta region, and unemployment variables had a positive and significant effect on investment in the Mamminasata region. Keywords: Gross Regional Domestic Product, Wages, Unemployment, Investment, Mamminasata